Potential of natural technologies for decentralised wastewater management in India. - Starkl, M.; Amerasinghe, Priyanie H.; Essl, L.; Jampani, M.; Kumar, D.; Asolekar, Shyam R. (International Water Association (IWA) Conference on Decentralised Wastewater Management in Asia, 2012)
High population growth, increasing urbanization and rapid economic development are exerting pressure on the already scarce water resources in India. Treatment and reuse of wastewater can play an important role in addressing some of the urban water challenges. Conventional treatment plants have many challenges, therefore, natural treatment systems (NTSs) are viewed as a cost-effective alternative, which are more suitable in the Indian context. This study builds on a desktop study of NTSs and presents a rapid sustainability assessment of 12 NTSs, highlighting the potential and viability of NTSs in India. The results show that the NTSs have a high potential for wastewater treatment. However, there are still gaps in knowledge related to aspects that hinder the sustainability of the systems. Risks associated with reuse of treated wastewater in agriculture, operational problems and social acceptance were perceived as frequent challenges. Self-sustaining financing methods and the use of by-products were viewed as added benefits.